B cell dysfunction in thalamus and brainstem involvement and high lactate caused by novel mutation of EARS2 gene - Yu Wen; Yanmei Huang; Wendi Zhang; Ping Chen; Xiufen Hu; Xin Xiong; Li Luo (Italian Journal of Pediatrics)
Abstract Purpose The EARS2 gene, a member of the mt-aaRS family, encodes mitochondrial glutamyl-tRNA synthetase (GluRS), which is involved in the synthesis of mitochondrial proteins. Pathogenic defects in EARS2 may cause mitochondrial OXPHOS deficiency, which is associated with a rare autosomal-recessive mitochondrial disease, leukoencephalopathy with thalamus and brainstem involvement and high lactate (LTBL). Methods In this study, clinical features were obtained, and whole-exome sequencing was conducted on a patient with LTBL. B- and T-cell immunophenotyping and protein expression were analyzed using flow cytometry, and B-cell metabolism was investigated using confocal microscopy. Results The patient with LTBL exhibited typical neurological manifestations, recurrent respiratory tract infections, and humoral immune disorders. Molecular analysis revealed a compound heterozygous novel mutation in c.1304T > A (p.L435Q) and a previously reported c.319 C > T (p.R107C) mutation of EARS2. The mutations led to protein structural modifications of EARS2. The patient also exhibited disrupted peripheral B-cell differentiation and B-cell receptor signal transduction. The EARS2 mutation led to decreased expression of CD38 and dysfunction of mitochondrial metabolism, with elevated reactive oxygen species levels in B cells. Conclusion We identified a novel mutation of the EARS2 gene in a patient with LTBL, expanding the mutation database. The mutation of EARS2 modified protein structure and impaired B-cell function, decreased CD38 expression, and led to dysfunction of mitochondrial metabolism, all of which may account for the recurrent respiratory tract infections and humoral immune disorders observed in LTBL.